2023
DOI: 10.1071/py22258
|View full text |Cite
|
Sign up to set email alerts
|

Exploring general practitioners’ perception of the value of natural history information and their awareness and use of guidelines’ resources to support antibiotic prescribing for self-limiting infections: a qualitative study in Australian general practice

Abstract: Background The newest version of the Therapeutic Guidelines’ antibiotic chapter introduced patient- and clinician-facing resources to support decision-making about antibiotic use for self-limiting infections. It is unclear whether general practitioners (GPs) are aware of and use these resources, including the natural history information they contain. We explored GPs’ perceptions of the value and their use of natural history information, and their use of the Therapeutic Guidelines’ resources (summary table, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, this information is missing in about 40% of guidelines [20], and sometimes the information provided in guidelines is not evidence-based [24]. In a recent qualitative study with Australian general practitioners, they identi ed the value of knowing natural history evidence and using it in consultations, but felt illprepared to do so without ready access to it [51]. A study of UK primary care patients found that natural history information is highly desired, but is the most common unmet need in a consultation [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, this information is missing in about 40% of guidelines [20], and sometimes the information provided in guidelines is not evidence-based [24]. In a recent qualitative study with Australian general practitioners, they identi ed the value of knowing natural history evidence and using it in consultations, but felt illprepared to do so without ready access to it [51]. A study of UK primary care patients found that natural history information is highly desired, but is the most common unmet need in a consultation [52].…”
Section: Discussionmentioning
confidence: 99%